Hubungan Pengetahuan Ibu Tentang Stimulasi Perkembangan Dengan Perkembangan Bayi Di Desa Tunggal Pager Kecamatan Pungging Kabupaten Mojokerto - Eny Susilawati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
this study, is identified in order to know whwther there is a relation between mothers knowledge on growths stimulations and babys growth in tunggal pager of Pungging, Mojokerto. and the result showed that mother who have high knowladge are about 13 (20,97%), idle knowledge are 33 (53,255) and low knowledge are 16 (25,8%), there was a correlation between mothers knowledge on growths stimulation and the babys growth. based on this research it was hoped and that mothers knowledge on growths stimulation could be improved by the mothers efforts themselves by reading growths aricels or by joining thr growths consultaion or seminars.